Transamidinase Activity of Hyphal Fractions of a Streptomycin-Producing Streptomyces griseus Strain and Enhancement of Enzyme Activity in a Nonproducing Mutant - Barabás, Gy. (1974)
The presence of transamidinase (TA-se) was demonstrated in Streptomyces griseus strain 45 which does not produce streptomycin (SM). This enzyme is involved in the biosynthesis of streptidine, a component of the SM molecule. TA-se is generally thought to be present only in SM-producing Streptomyces strains. The recent results are, however, in agreement with out previous data which showed the presence of streptidine in the isolated cell wall of SM-nonproducing strain 45. The TA-se activity of this strain is very low, but we were able to increase it by addition of arginine or by increasing the incubation with myo-inositol. The addition of these substances to the cultures of SM-nonproducing S. griseus strains, which hitherto were deficient in TA-se, may serve as a method for detecting the presence of this enzyme. In an incubation system in which the hyphae of an SM-producing strain of S. griseus had been blended and separated by density gradient centrifugation, certain hyphal fractions had been combined, and their SM production and TA-se activity had been measured, we were unable to find any close correlation between TA-se activity and SM-producing capacity. The hyphal fractions and their combination did not show strict parallelism between TA-se activity and the level of SM production.